A Multiwavelength View of the Rapidly Evolving SN 2018ivc: An Analog of SN IIb 1993J but Powered Primarily by Circumstellar Interaction - Maeda, Keiichi (2022)
SN 2018ivc is an unusual Type II supernova (SN II). It is a variant of SNe IIL, which might represent a transitional case between SNe IIP with a massive H-rich envelope and SNe IIb with only a small amount of the H-rich envelope. However, SN 2018ivc shows an optical light-curve evolution more complicated than that of canonical SNe IIL. In this paper, we present the results of prompt follow-up observations of SN 2018ivc with the Atacama Large Millimeter/submillimeter Array. Its synchrotron emission is similar to that of SN IIb 1993J, suggesting that it is intrinsically an SN IIb-like explosion of an He star with a modest (∼0.5-1M ⊙) extended H-rich envelope. Its radio, optical, and X-ray light curves are explained primarily by the interaction between the SN ejecta and the circumstellar material (CSM); we thus suggest that it is a rare example (and the first involving the “canonical” SN IIb ejecta) for which the multiwavelength emission is powered mainly by the SN-CSM interaction. The inner CSM density, reflecting the progenitor activity in the final decade, is comparable to that of SN IIb 2013cu, which shows a flash spectral feature. The outer CSM density, and therefore the mass-loss rate in the final ∼200 yr, is higher than that of SN 1993J by a factor of ∼5. We suggest that SN 2018ivc represents a missing link between SNe IIP and SNe IIb/Ib/Ic in the binary evolution scenario.